2019
DOI: 10.1186/s13287-019-1442-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-644-5p carried by bone mesenchymal stem cell-derived exosomes targets regulation of p53 to inhibit ovarian granulosa cell apoptosis

Abstract: BackgroundThis article aims to reveal the therapeutic effects and potential mechanisms of bone mesenchymal stem cell (BMSC)-derived exosomes on premature ovarian failure (POF).MethodsExosomes were collected from BMSCs and were used to treat cisplatin-induced POF mouse models. Pathological changes of ovarian tissue were detected by using HE staining and by Western blot that detected the expression of apoptosis-related proteins. In cisplatin-induced primary granulosa cell injury, exosomes were co-cultured with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 29 publications
2
84
0
Order By: Relevance
“…In this study, hAEC-derived exosomes inhibited granulosa cell apoptosis, protected ovarian vasculature, and maintained the number of primordial follicles in the chemotherapy-damaged ovaries. Similar results were shown by Sun and colleagues [43] who demonstrated the inhibition of ovarian granulosa cells apoptosis by negatively regulating p53 by the administration of BMSC-derived exosomal miR-644-5p into a cisplatin-induced POF mouse model. These results indicated that MSC-derived exosomal miRNA can play a key role in the restoration of ovarian function in chemotherapy-induced animal models.…”
Section: Direct Utilization Of Undifferentiated Stem Cells In Curing supporting
confidence: 86%
See 3 more Smart Citations
“…In this study, hAEC-derived exosomes inhibited granulosa cell apoptosis, protected ovarian vasculature, and maintained the number of primordial follicles in the chemotherapy-damaged ovaries. Similar results were shown by Sun and colleagues [43] who demonstrated the inhibition of ovarian granulosa cells apoptosis by negatively regulating p53 by the administration of BMSC-derived exosomal miR-644-5p into a cisplatin-induced POF mouse model. These results indicated that MSC-derived exosomal miRNA can play a key role in the restoration of ovarian function in chemotherapy-induced animal models.…”
Section: Direct Utilization Of Undifferentiated Stem Cells In Curing supporting
confidence: 86%
“…Despite having the ability to differentiate into many other cell types under targeted lineage-specific culture conditions, stem cells have shown promising results in curing diseases by their direct insertion into disease models. A number of neonatal and adult sources including bone marrow [43,47,48,55,108,109], endometrial [110], amnion [53,111], amniotic fluid [4], amniotic epithelium [44], menstrual blood [9,51], umbilical cord [56,112], umbilical cord blood [54], umbilical cord vein [52], placenta [49], chorionic plate [50], adipose [113], and skin [46] have shown the restoration of ovarian function in many reproductive disease models. Due to their low immunogenicity, migratory, and homing properties, MSCs have been widely used to restore ovarian functions in POF models.…”
Section: Direct Utilization Of Undifferentiated Stem Cells In Curing mentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes are important vehicles for intercellular communication, and as such, are critical for many physiological functions. Recent studies indicated that exosomal miRNAs can regulate intercellular signal transduction and control molecular activities in different diseases [ 60 , 61 , 62 , 63 ]. Two studies have demonstrated a role of miRNAs carried by BMSCs-derived exosomes in promoting the recovery of ovarian function in a POF animal model [ 61 , 62 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%